2h + 2h + 2h = 6h
6h - 7 = 17... The value of 6h MUST equal 24, since 24 - 7 = 17. Therefore h MUST equal 4, because 6 x 4 = 24.
3h + 20 - h + 5 = 2h + 25
6h+4g
It is nothing more than the product of the two, (A + H + 1)(A + 1) = A2 + AH + 2A + H + 1.
- 3h - 2h + 6h + 9 = h + 9
If you mean: 6h+7 then 6*5 plus 7 = 37
3tx + 6t + 3hx +6h = 3(tx + 2t +hx +2h) = 3[t(x + 2) + h(x + 2)] = 3(x + 2)(t + h)
6h = 72 h = 72/6 h = 12
This is a linear equation with one unknown and can be solved as follows. 6h + 2 = 1.......subtract 2 from both sides 6h = -1............divide both sides by 6 h = -1/6.
6h
29
2h + 2h + 2h = 6h
6h-t
6h 8min
22h plus 3
6h - 7 = 17... The value of 6h MUST equal 24, since 24 - 7 = 17. Therefore h MUST equal 4, because 6 x 4 = 24.